A composite free-cutting steel containing sulfur, tin and titanium and a vacuum induction preparation method thereof

Through vacuum induction smelting, the addition amount and composition ratio of sulfur, tin and titanium elements were adjusted, and composite easy-cut steel containing sulfur-tin titanium was prepared, which solved the problem of chip breakage in the existing easy-cut steel during the cutting process, and achieved both high cutting performance and good mechanical properties.

CN116121627BActive Publication Date: 2025-04-29CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211517894.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2025-04-29
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

Existing easy-to-cut steels are prone to chip breakage during cutting, and the form and distribution of manganese sulfide are not conducive to improving cutting performance.

Method used

Through vacuum induction smelting, the addition amount and composition ratio of sulfur, tin and titanium elements are reasonably regulated, and the morphology, size, aspect ratio and distribution method of sulfide are controlled to prepare composite easy-cut steel containing sulfur-tin titanium.

Benefits of technology

The cutting performance and mechanical properties of steel are improved, making it suitable for the manufacturing of parts in industries such as automobiles, high-speed rail, home appliances and office equipment, reducing machining costs and production difficulties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116121627B_ABST
    Figure CN116121627B_ABST
Patent Text Reader

Abstract

The invention discloses a vacuum induction preparation method of a composite free-cutting steel containing sulfur, tin and titanium, which comprises the following steps: preheating the alloy raw material; then vacuum melting the raw material with a specific composition ratio; mixing the smelted molten steel with graphite, ferrosilicon, ferromanganese, ferrophosphorus, ferromolybdenum and ferrotitanium in an inert atmosphere, mixing the molten steel with metal tin, and finally mixing the ferrosulphur, and standing the mixture to obtain a mixed molten steel; pouring the molten steel into a mold, cooling the molten steel to room temperature to obtain a steel ingot, and air cooling the molten steel to room temperature to obtain a composite free-cutting steel containing sulfur, tin and titanium. The invention improves the morphology and distribution of sulfides in the steel by reasonably adjusting the addition amount of sulfur, tin and titanium elements in the steel making process, and increases the generation ratio of small-sized spindle-shaped sulfides, so that the proportion of sulfides with an aspect ratio of ≤3 in the prepared free-cutting steel is as high as 95%, and the steel has high strength, high plasticity and high cutting performance, thereby broadening the market application scope of free-cutting steel and improving the competitiveness of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel processing, and in particular to a composite free-cutting steel containing sulfur, tin and titanium and a vacuum induction preparation method thereof. Background Art

[0002] Free-cutting steel refers to alloy steel that adds a certain amount of one or more free-cutting elements such as sulfur, phosphorus, lead, calcium, selenium, tellurium, etc. to improve cutting performance. According to the different free-cutting elements contained, free-cutting steel can be divided into sulfur-based free-cutting steel, lead-based free-cutting steel, titanium-based free-cutting steel and composite free-cutting steel. Sulfur-based free-cutting steel is the earliest free-cutting steel to be introduced, with the largest amount and the widest application so far, accounting for more than 70% and 90% of the total free-cutting steel output in the world and my country respectively. Sulfur-based free-cutting steel is mainly used in complex parts such as bolts, nuts, pipe joints, automotive brake parts, spring seats and molds. These complex parts need to be cut on CNC machine tools. In order to extend the service life of the tool, reduce processing costs and improve production efficiency, the steel must have good cutting performance. The sulfur in sulfur-based free-cutting stainless steel mainly exists in the form of manganese sulfide. Manganese sulfide inclusions can act as a stress concentration source to induce many microcracks in the matrix, reduce cutting resistance and cause the steel to break easily during turning.

[0003] The researchers first classified the manganese sulfide in the steel casting structure, and divided it into three categories according to the different morphology and distribution of manganese sulfide: the first category is spherical composite inclusions, which are randomly distributed and exist in steel without aluminum deoxidation; the second category is short rod-shaped, distributed in chains or nets along the grain boundaries, and exists in steel deoxidized with a small amount of aluminum; the third category is blocky, irregularly distributed, and exists in steel with high aluminum addition and residual aluminum; later, researchers added a fourth category: dendritic sulfide. Some researchers have studied the influence of alloying elements on the morphology of manganese sulfide in free-cutting steel, and classified manganese sulfide: the first category is spherical (category I), formed by partial crystal reaction; the second category is short rods or dendritic (category II), formed by eutectic reaction; the third category is irregular (category III), generated by pseudo-eutectic reaction. The size, morphology and distribution of manganese sulfide in sulfur-containing free-cutting stainless steel have a significant effect on the mechanical properties of the steel. In order to obtain the best cutting performance, it is hoped that spherical or spindle-shaped sulfide inclusions with a relatively small aspect ratio are obtained in production. Such inclusions are not easily deformed during the rolling process due to their low plasticity, and can remain spindle-shaped or ellipsoidal after the matrix is ​​deformed, which is very beneficial to improving the cutting performance. However, the slender strips of manganese sulfide with an aspect ratio exceeding 4:1 not only destroy the continuity of the matrix, but also cause the cutting chips to stick together and reduce the surface quality of the workpiece. Free-cutting stainless steel is prone to generate slender strips of manganese sulfide after forging deformation, causing anisotropy of the steel and reducing the comprehensive mechanical properties of the steel.

[0004] Tin and lead are in the same main group, with similar physical and chemical properties, and are a kind of free-cutting elements. Tin-containing steel has a brittle valley near 275°C. When cutting tin-containing steel, when the cutting temperature is near the brittle valley, the steel tends to fracture brittlely, and it is easy to produce chip breakage during the cutting process, thereby improving the cutting performance of the steel. Tin has a high boiling point, low vapor pressure, is not easy to volatilize and is non-toxic. The production and use of tin-containing free-cutting steel will not have an adverse impact on the ecology. It is a new "green and environmentally friendly" steel. Tin has extensive resources and is reasonably priced. It is an ideal substitute for lead. In addition, titanium can improve the morphology and distribution of sulfides in free-cutting stainless steel. In the nucleation process of sulfides, titanium can serve as the nucleation core of sulfides during the solidification of molten steel, promoting the nucleation of sulfides. Titanium oxides, nitrides and carbonitrides can also refine grains and improve the mechanical properties of steel. However, it is difficult to achieve high cutting performance with a low tin content, while a high tin content will cause tin to segregate at the austenite grain boundaries during hot rolling, causing material brittleness and having a harmful effect on process performance. Excessive titanium content will form large high-melting-point titanium nitrides, reducing the cutting performance of steel. Therefore, exploring how to reasonably add tin and titanium in the steelmaking process so that they can improve the mechanical properties of the composite free-cutting steel without affecting the cutting performance of the steel has become a key technology for producing high-strength and high-free-cutting steel products. Summary of the invention

[0005] The purpose of the present invention is to provide a method and amount of sulfur, tin and titanium elements in the process of preparing free-cutting steel by reasonably regulating the vacuum induction smelting method, effectively controlling and improving the morphology, size, aspect ratio and distribution of sulfides in free-cutting steel, so that the prepared sulfur-tin-titanium composite free-cutting steel has good mechanical properties and ultra-high cutting performance, thereby making it suitable for manufacturing parts for industries such as automobiles, high-speed railways, home appliances and office equipment, which can effectively reduce machining costs, improve production efficiency and product competitiveness.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A vacuum induction preparation method for composite free-cutting steel containing sulfur, tin and titanium, the method comprising:

[0008] Preheating the alloy raw materials;

[0009] The alloy raw materials after preheating are vacuum melted in a specific composition ratio;

[0010] The molten steel after vacuum melting is sequentially mixed with graphite, ferrosilicon, ferromanganese, ferrophosphorus, ferromolybdenum and ferrotitanium under an inert atmosphere, then mixed with metallic tin, and finally mixed with ferrosulphide, and then allowed to stand to obtain a mixed molten steel;

[0011] pouring the mixed molten steel into a mold, and obtaining a steel ingot after cooling to room temperature;

[0012] The steel ingot is annealed and air-cooled to room temperature to obtain a sulfur-tin-titanium composite free-cutting steel.

[0013] As a further improvement of the present invention, the preheating treatment conditions are: heating the alloy raw material to 150° C. to 250° C. and keeping the temperature for 3 h to 5 h.

[0014] As a further improvement of the present invention, the preheating treatment conditions are: heating the alloy raw material to 250° C. and keeping it warm for 5 hours.

[0015] As a further improvement of the present invention, the composition ratio of the alloy raw material is: in mass percentage, 0.01% to 0.1% C, 0.1% to 0.5% Si, 0.5% to 5% Mn, 0.1% to 0.5% Ni, 10.0% to 20.0% Cr, 0.1% to 1.0% S, 0.005% to 0.0015% Mo, 0.01% to 0.015% O, 0.01% to 0.015% N, 0.0001% to 0.005% H, 0.1% to 0.5% Sn, 0.001% to 0.05% Ti, P≤0.01%, and the balance is Fe and unavoidable impurities.

[0016] As a further improvement of the present invention, the composition of the alloy raw material includes:

[0017] The mass percentage of S is 0.1% to 0.5%;

[0018] The mass percentage content of Sn is 0.1% to 0.3%;

[0019] The mass percentage content of Ti is 0.01% to 0.02%.

[0020] As a further improvement of the present invention, the vacuum degree during vacuum smelting is controlled to be ≤3Pa; the temperature is gradually increased to a smelting temperature of 1580°C to 1620°C, and after smelting is completed, refining is performed at 1580°C to 1600°C and the temperature is kept for 10min to 20min.

[0021] As a further improvement of the present invention, the smelting temperature is controlled at 1620°C, and after the smelting is completed, refining is carried out at 1600°C and the temperature is kept for 10 minutes.

[0022] As a further improvement of the present invention, the inert atmosphere condition is controlled to be an argon atmosphere of 10000-30000Pa.

[0023] As a further improvement of the present invention, the pouring temperature is controlled to be 1500° C. to 1550° C., and the casting time is 1 min to 3 min.

[0024] As a further improvement of the present invention, the annealing temperature is controlled to be 800° C. to 900° C., and the holding time is 1 h to 3 h.

[0025] As a further improvement of the present invention, the annealing temperature is controlled to be 850° C. and the holding time is 2 h.

[0026] The present invention also provides a sulfur-tin-titanium composite free-cutting steel, and the sulfur-tin-titanium composite free-cutting steel is prepared by any of the preparation methods described above.

[0027] Technical effects and advantages of the present invention:

[0028] The vacuum induction preparation method of the composite free-cutting steel containing sulfur, tin and titanium of the present invention comprises the following steps: preheating the alloy raw material; vacuum melting the preheated alloy raw material in a specific composition ratio; mixing the vacuum-melted molten steel with graphite, ferrosilicon, ferromanganese, ferrophosphorus, ferromolybdenum and ferrotitanium in an inert atmosphere, mixing with metallic tin, and finally mixing with ferrosulphur, and standing to obtain a mixed molten steel; pouring the mixed molten steel into a mold, cooling to room temperature to obtain a steel ingot; annealing the steel ingot, and air cooling to room temperature to obtain a composite free-cutting steel containing sulfur, tin and titanium. In the above manner, the present invention effectively improves the morphology and distribution of sulfides in steel and increases the proportion of small-sized spindle-shaped sulfides by reasonably adjusting the addition amounts of sulfur, tin and titanium elements in the steelmaking process. The proportion of sulfides with an aspect ratio of ≤3 in the prepared sulfur-tin-titanium composite free-cutting steel is as high as 95%, which can combine high strength, high plasticity and high cutting performance. Therefore, it can be used in the field of parts manufacturing technology in industries such as automobiles, high-speed railways, home appliances and office equipment, effectively reducing machining costs, improving production efficiency and product competitiveness.

[0029] The vacuum induction preparation method of the sulfur-containing tin-titanium composite free-cutting steel of the present invention can prepare a smaller-sized sulfur-containing tin-titanium composite free-cutting steel ingot, thereby reducing the processing difficulty of the material, shortening the preparation cycle, and improving the material quality. In addition, the smelting process of the present invention is simple, the process is short, the raw materials of the steel are widely available, and the production cost of the sulfur-containing tin-titanium composite free-cutting steel can be reduced.

[0030] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a flow chart of the vacuum induction preparation method of the composite free-cutting steel containing sulfur, tin and titanium of the present invention;

[0032] Figure 2This is a SEM morphology of sulfides in the sulfur-tin-titanium composite free-cutting steel prepared in an embodiment of the present invention;

[0033] Figure 3 This is an optical microscope morphology of sulfides in the sulfur-tin-titanium composite free-cutting steel prepared in an embodiment of the present invention;

[0034] Figure 4 This is a surface scanning energy spectrum diagram of Ti sulfide in the sulfur-tin-titanium composite free-cutting steel prepared in an embodiment of the present invention;

[0035] Figure 5 The stress-strain curve of the sulfur-tin-titanium composite free-cutting steel prepared in the embodiment of the present invention;

[0036] Figure 6 This is a SEM image of the tensile fracture of the sulfur-tin-titanium composite free-cutting steel prepared in an embodiment of the present invention;

[0037] Figure 7 The chips are the cutting chips of the sulfur-tin-titanium composite free-cutting steel prepared in the embodiment of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In order to solve the deficiencies of the prior art, the present invention provides a vacuum induction preparation method of a composite free-cutting steel containing sulfur, tin and titanium, and provides an environmentally friendly free-cutting steel. In order to obtain ultra-high cutting performance, the present invention simultaneously adds sulfur, tin and titanium elements on the basis of the prior art, prepares "super" free-cutting steel by vacuum smelting, and also properly regulates the composition ratio of elements such as Mn, S, Sn and Ti, thereby ensuring good mechanical properties of the material and obtaining excellent cutting performance. Specifically, the present invention effectively controls and improves the morphology, size, aspect ratio and distribution of sulfides in free-cutting steel by reasonably adding the content of S, Sn and Ti elements and the addition time and order of S, Sn and Ti alloys during the smelting process. The sulfide morphology in the composite free-cutting steel containing sulfur, tin and titanium prepared by the method of the present invention is mainly spindle-shaped, the proportion of sulfides with an aspect ratio of ≤3 is more than 95%, the tensile strength is ≥700MPa, the yield strength is ≥600MPa, the cross-sectional shrinkage is ≥30%, the elongation after fracture is ≥25%, and the impact toughness is ≥15J. The sulfur-tin-titanium composite free-cutting steel prepared by the present invention having both high strength and high cutting performance is suitable for manufacturing parts in industries such as automobiles, high-speed railways, home appliances and office equipment, and can effectively reduce machining costs, improve production efficiency and product competitiveness.

[0040] The technical solution of the present invention is as follows:

[0041] See also Figure 1 As shown, the present invention provides a vacuum induction preparation method of a sulfur-tin-titanium composite free-cutting steel, wherein the constituent elements and their element mass percentages are: 0.01% to 0.1% C, 0.1% to 0.5% Si, 0.5% to 5% Mn, 0.1% to 0.5% Ni, 10.0% to 20.0% Cr, 0.1% to 1.0% S, 0.005% to 0.0.015% Mo, 0.01% to 0.015% O, 0.01% to 0.015% N, 0.0001% to 0.005% H, 0.1% to 0.5% Sn, 0.001% to 0.05% Ti, P≤0.01%, and the rest are Fe and unavoidable impurities.

[0042] Furthermore, the mass percentage content of S is preferably 0.1% to 0.5%;

[0043] Furthermore, the mass percentage content of Sn is preferably 0.1% to 0.3%.

[0044] Furthermore, the mass percentage content of Ti is preferably 0.01% to 0.02%.

[0045] A. Preparation before smelting:

[0046] Before smelting, bake all the alloy raw materials required for smelting to 150℃~250℃ and keep them warm for 3h~5h. Before opening the furnace, test run all vacuum pumps, water cooling systems, rotating devices, electrical cabinet systems, and sealing devices, and ensure that they operate normally;

[0047] Furthermore, in step a, the baking temperature of the alloy raw material is preferably 250° C., and the holding time is preferably 5 h.

[0048] B.Weighing:

[0049] The raw materials are accurately weighed according to the quantity specified in the ingredients. Large pieces of materials such as high-purity iron and metallic chromium are weighed using a 100Kg electronic scale. Small quantities of materials such as graphite, metallic silicon, metallic manganese, ferrophosphorus, ferrosulfur, ferromolybdenum, nickel plate, metallic tin, and ferrotitanium are weighed using a 200g electronic scale. Each material is polished with a grinding wheel before weighing to remove the oxide scale on its surface. Each furnace is weighed with 140Kg of ingredients and is checked again before loading into the furnace.

[0050] C. Loading:

[0051] The materials should be loaded as tightly as possible to avoid bridging. Loading order: high purity iron, ferrochrome, and nickel plates are loaded with the furnace. Graphite, metallic silicon, metallic manganese, ferrophosphorus, ferrosulfur, ferromolybdenum, metallic tin, and ferrotitanium are placed in separate silos of the vacuum induction furnace.

[0052] D. Melting:

[0053] When the vacuum degree of the melting chamber is ≤1Pa, start the vacuum induction furnace, heat the charge, and gradually start to melt the charge. Slowly increase the power to slowly melt the charge. The process steps of slowly increasing the power in the initial stage of smelting are as follows: power 10kW, lasting 5min~10min; power 20kW, lasting 15min~20min; power 60kW, lasting 10min~20min; power 70kW, lasting 10min~20min; power 100kW, lasting 10min~20min; power 120kW, continue smelting until the high-purity iron, ferrochrome, and nickel plate are all melted with the charge.

[0054] E. Refining:

[0055] After the charge is melted, continue to heat up to 1580℃~1620℃. After appropriately reducing the power supply, keep the temperature of the molten steel at 1580℃~1600℃ for 10min~20min to remove the oxide film. During the refining period, always keep the vacuum degree of the melting chamber ≤3Pa.

[0056] Furthermore, after the charge is melted, the temperature of the molten steel is raised to a preferred temperature of 1620°C, and after the power supply is appropriately reduced, the temperature of the molten steel is maintained at a preferred temperature of 1600°C, and the holding time is preferably 10 minutes.

[0057] F. Add alloy:

[0058] After refining, fill the argon gas to 10000~30000Pa, add graphite, ferrosilicon, ferromanganese, ferrophosphorus, ferromolybdenum, ferrotitanium, metallic tin in order, and finally add ferrosulphur. After adding ferrosilium, carry out high-power electromagnetic stirring for 3min~5min. After adding metallic tin, carry out high-power electromagnetic stirring for 3min~5min. After adding ferrosulphur, carry out high-power electromagnetic stirring for 3min~5min, and then let it stand for 3min~5min.

[0059] Furthermore, after the refining is completed, the amount of argon gas charged is preferably 25000Pa; high-power electromagnetic stirring is performed after the addition of ferrotitanium, and the electromagnetic stirring time is preferably 5 minutes. High-power electromagnetic stirring is performed after the addition of metallic tin, and the electromagnetic stirring time is preferably 5 minutes. High-power electromagnetic stirring is performed after the addition of ferrosulphur, and the electromagnetic stirring time is preferably 5 minutes, and then the standing time is preferably 3 minutes.

[0060] G. Pouring:

[0061] The casting temperature of the molten steel is 1500℃~1550℃, the casting time is 1min~3min, and it is cast into a φ200mm×400mm metal mold. The molten steel solidifies in the furnace and cools to room temperature to obtain a φ200mm ingot.

[0062] Furthermore, the casting temperature of the molten steel is preferably 1550° C., and the casting time is preferably 2 minutes.

[0063] H. Annealing treatment:

[0064] The ingot is placed in a muffle furnace for annealing at a temperature of 800°C to 900°C for a holding time of 1h to 3h. After the holding time is completed, the ingot is air-cooled to room temperature.

[0065] Furthermore, the annealing temperature is preferably 850° C., and the holding time is preferably 2 h.

[0066] Principle of the present invention:

[0067] The influence of each element composition in the present invention on the cutting performance and mechanical properties of the composite free-cutting steel containing sulfur, tin and titanium:

[0068] C: Carbon is one of the important elements for improving the strength and hardness of free-cutting stainless steel. The carbon content directly affects the strength, plasticity, toughness and welding performance of steel. When the carbon content in steel is too low, the ferrite content will increase, and the strength and hardness of the steel will decrease. Since the steel is too soft and tough, the cutting chips will easily stick to the knife, and its cutting performance will decrease. On the contrary, when the carbon content in steel is too high, its hardness will increase, which will also cause tool wear and reduce the cutting performance of the steel. Therefore, the C content in the present invention is controlled within the range of 0.01% to 0.1%.

[0069] Si: Silicon plays a major role in deoxidation in free-cutting stainless steel. It is used to control the oxygen content in free-cutting stainless steel and can improve the yield strength and work hardening rate of steel. It can affect the sulfide inclusion deformation in steel and the cutting performance of steel. Too high silicon content is easy to generate silicate inclusions, which will cause tool wear and reduce cutting performance. Too high silicon content will also cause a large amount of oxide scale to be generated in the steel during hot working, reduce the surface quality of the steel, promote phosphorus precipitation from the matrix, form phosphide film at the grain boundary, and deteriorate the hot working property of steel. Therefore, it is necessary to reasonably control the silicon content in free-cutting stainless steel. In the present invention, the Si content is controlled within the range of 0.1% to 0.5%.

[0070] Mn: Manganese is one of the important elements for improving the machinability of free-cutting stainless steel. Manganese is easily combined with sulfur to form manganese sulfide phase, which is the most important free-cutting phase in free-cutting stainless steel. Too high manganese content will increase the toughness of steel and reduce cutting performance. Too low manganese content will result in less manganese sulfide, which is not conducive to improving cutting performance. Therefore, the Mn content in the present invention is controlled within the range of 0.5% to 5%.

[0071] Ni: Nickel is an excellent corrosion-resistant material and an important alloying element for free-cutting steel. Nickel can both increase the strength of steel and keep the steel material in good plasticity and toughness. In the present invention, the Ni content is controlled within the range of 0.1% to 0.5%.

[0072] Cr: The main function of chromium in steel is to improve the corrosion resistance of steel. Chromium can also improve the hardenability of steel, so that the steel has better comprehensive mechanical properties after quenching and tempering. Chromium can also improve the strength of steel, especially when other alloying elements are added, the effect will be more significant. However, too high chromium content in steel will increase the hardness of steel, and too high hardness will affect the cutting performance of steel. Therefore, the Cr content in the present invention is controlled within the range of 10% to 20%.

[0073] S: Sulfur is the most important free-cutting element in free-cutting stainless steel. Sulfur is mainly distributed in the steel matrix in the form of sulfides. The size, content, morphology and distribution of sulfides directly affect the cutting performance of the steel. When the sulfur content is lower than 0.1%, sufficient sulfides cannot be generated in the steel, and the requirements of high cutting performance cannot be met; on the contrary, when the sulfur content exceeds 1.0%, its hot working performance will be reduced and it is easy to cause sulfur segregation in the center of the ingot. Therefore, the S content in the present invention is controlled within the range of 0.1% to 1.0%.

[0074] Mo: Mo can refine the grains of steel and improve hardenability and heat resistance. When molybdenum coexists with chromium and manganese, it can reduce or inhibit the temper brittleness caused by other elements. Therefore, the Mo content in the present invention is controlled within the range of 0.005% to 0.0015%.

[0075] Sn: Tin and iron are mutually soluble in high-temperature liquid state, and the maximum solubility in solid α-Fe reaches 17.7%. However, as the temperature decreases, the solubility of tin in steel decreases. Below 200°C, the solid solubility of Sn in α-Fe decreases sharply. In theory, FeSn will be produced, but Sn diffusion is very slow. Sn exists in the form of solid solution without obvious macro-segregation. Only a small part forms FeSn, but it is difficult to detect in practice. Tin-containing steel has a brittle valley near 275°C. When cutting, the cutting temperature is near the brittle valley, the steel tends to fracture brittlely, and it is easy to produce chip breakage during the cutting process, thereby improving the cutting performance of the steel. The United States has developed a free-cutting steel that uses tin instead of lead and put it on the market. The mechanical properties of the cutting steel are basically the same as those of the lead-containing free-machining steel, and the steel is easier to cut. The chemical composition required by the U.S. patent "Tin-bearing free-machining steel" (US 5961747, Oct. 5, 1999) has a Sn content of 0.04% to 0.08%. Compared with the U.S. patent, the steel provided by the present invention has a main feature that the Sn content is greatly increased, and Sn is used as the main added element to improve the cutting performance of the steel. Therefore, the Sn content in the present invention is controlled within the range of 0.1% to 0.5%.

[0076] Ti: Titanium can improve the morphology and distribution of sulfides in free-cutting stainless steel. Titanium can serve as the nucleation core of sulfides during the solidification of molten steel and promote sulfide nucleation. Titanium oxides, nitrides and carbonitrides can also refine grains and improve the mechanical properties of steel. However, too high a titanium content will form larger high-melting-point titanium nitrides, reducing the cutting performance of the steel. Therefore, the Ti content in the present invention is controlled within the range of 0.001% to 0.02%.

[0077] O: Oxygen in free-cutting stainless steel mainly plays a role in regulating the morphology of sulfides. Under normal circumstances, when the oxygen content is higher than 0.02%, the first type of sulfides are formed in the steel (spherical, irregularly distributed, inclusions are single-phase or two-phase, often present in steel without aluminum deoxidation, which can significantly improve the cutting performance of the steel); when the oxygen content in the steel is between 0.004% and 0.01%, the second type of sulfides are easily formed (short rods, chain or network distribution along the grain boundary, often present in steel deoxidized with a small amount of aluminum); when the oxygen content in the steel is less than 0.004%, the third type of sulfides are easily formed (blocky, irregularly distributed, often present in steel with high aluminum addition and residual aluminum). The three types of sulfides often appear in the steel at the same time, including spherical, blocky and short rod-shaped; among them, the first type of sulfides is most beneficial to the cutting performance of the steel. Oxygen in sulfide will form (Mn, Fe) (S, O) composite inclusions with other elements. Such inclusions have low plasticity and are not easily deformed during hot working deformation. They can maintain spindle and spherical shapes, which is beneficial to improving cutting performance. However, too high oxygen content will also affect the surface quality of easy-to-cut stainless steel, produce subcutaneous bubbles, and cause serious component segregation in the center of the ingot. If the oxygen content in the molten steel is too high, the water inlet of the molten steel will be blocked during continuous casting, and too high a content of hard oxide inclusions will have an adverse effect on tool wear, ultimately affecting the cutting performance of the steel. Increased oxygen content will also reduce the high-temperature mechanical properties of the test steel. By reasonably controlling the oxygen content to generate oxides with sulfur-containing inclusion-shaped cores in the steel, the effect of regulating and improving the size, quantity, distribution and morphology of sulfides can be achieved. Therefore, taking into account the combination of components, the O content in the present invention is easily controlled within the range of 0.01% to 0.015%.

[0078] P: Phosphorus can improve the strength and hardenability of steel, but too high a content of phosphorus can reduce the cutting performance of steel and lead to a decrease in hot working performance. Therefore, in the present invention, the phosphorus content is controlled within a range of less than 0.01%.

[0079] N: Nitrogen can combine with titanium to form nitrides and carbonitrides. These nitrides and carbonitrides often nucleate and precipitate at the grain boundaries, which is beneficial to refine the grains and improve the strength of the steel. During the solidification of molten steel, nitrides and carbonitrides can also serve as the cores for the nucleation of sulfides, which is beneficial to improve the distribution of sulfides, thereby improving the cutting performance of free-cutting stainless steel. However, when the nitrogen content is too high, large particle inclusions are easily formed, which reduces the cutting performance of the steel. Therefore, the N content in the present invention is controlled within the range of 0.01% to 0.015%.

[0080] The vacuum induction preparation method of the composite free-cutting steel containing sulfur, tin and titanium provided by the present invention is illustrated below with reference to specific embodiments:

[0081] The chemical composition of sulfur-containing tin-titanium composite free-cutting steel is as follows: C: 0.01%, Si: 0.3%, Mn: 1.0%, Cr: 13.1%, Ni: 0.4%, S: 0.3%, O: 0.01%, Mo: 0.01%, Sn: 0.3%, H: 0.0047%, Ti: 0.01%, N: 0.01%, O: 0.01%, P: 0.008% (wt%); the rest are Fe and unavoidable impurities; according to the technical scheme of the present invention, high-purity iron, ferrochrome, nickel plate, graphite, metallic silicon, metallic manganese, ferrophosphorus, ferrosulfur, ferromolybdenum, metallic tin and ferrotitanium are used as alloy raw materials, and the material list of each alloy raw material is shown in Table 1.

[0082] Table 1 Composition of each raw material

[0083] Al C Cr Ni Fe Mn P S Si Mo Sn Ti Manganese Metal 0 0.053 0 0 2.8 97.17 <0.1 0.021 0.4 0 0 0 Silicon Metal 0.3 0.023 <0.1 0 3.6 0 0.8 <0.003 95.44 0 0 0 Ferromolybdenum 0 0.07 0 0 0 0 0 0 0.242 56.07 0 0 Chromium 0.024 0.032 99.2 0 0.568 0 <0.01 0.0044 0.127 0 0 0 Iron Sulfide 0 0.12 0 0 36.75 0.2 <0.1 26 0.5 0 0 0 Ferrophosphorus 0 0 0 0 75 0 25 0 0 0 0 0 Tin Metal 0 0 0 0 0.01 0 0 0 0 0 99.9 0 graphite 0 97.5 0 0 0 0 0 0 0 0 0 0 Nickel Plate 0 0 0 99.98 0 0 0 0 0 0 0 0 Ferrotitanium 0 0.05 0 0 72 0 0.048 0 0.02 0 0 27.9 High purity iron 0 0.003 0.01 0 99.94 0.04 0.004 0.001 0 0 0 0

[0084] (1) Preparation before smelting: Before smelting, bake all the alloy raw materials required for smelting to 250℃ for 5 hours. Before opening the furnace, test run all vacuum pumps, water cooling systems, rotating devices, electrical cabinet systems, and sealing devices to ensure that they operate normally.

[0085] (2) Weighing: Weigh the raw materials accurately according to the quantity specified in the batching list. Use a 100 kg electronic scale to weigh large pieces of materials such as high-purity iron and metallic chromium. Use a 200 g electronic scale to weigh small amounts of materials such as graphite, metallic silicon, metallic manganese, ferrophosphorus, ferrosulfur, ferromolybdenum, nickel plate, metallic tin, and ferrotitanium. Grind each material with a grinding wheel before weighing to remove the surface oxide scale. Each furnace is loaded with 140 kg of materials. Check again before loading. The batching list of alloy raw materials is shown in Table 2.

[0086] Table 2 Alloy raw material ingredients list

[0087] alloy material Weight / Kg High purity iron 110.6 graphite 0.179 Silicon Metal 0.58 Manganese Metal 2.05 Ferrophosphorus 0.06 Iron Sulfide 2.3 Ferromolybdenum 0.028 Chromium 23.1 Nickel Plate 0.56 Tin Metal 0.525 Ferrotitanium 0.057

[0088] (3) Loading: Loading should be as tight as possible to avoid bridging. The loading order is: high purity iron, ferrochrome, and nickel plates are loaded with the furnace, and graphite, metallic silicon, metallic manganese, ferrophosphorus, ferrosulfur, ferromolybdenum, metallic tin, and ferrotitanium are placed in separate silos of the vacuum induction furnace.

[0089] (4) Melting: When the vacuum degree of the melting chamber is ≤1Pa, start the vacuum induction furnace, heat the charge, and melt the charge gradually and slowly. Slowly increase the power to make it melt slowly with the charge. The process steps of slowly increasing the power in the initial stage of melting are as follows: power 10kW, lasting 10min; power 20kW, lasting 20min; power 60kW, lasting 20min; power 70kW, lasting 20min; power 100kW, lasting 20min; power 120kW, continue melting until the high-purity iron, ferrochrome, and nickel plate are all melted with the charge.

[0090] (5) Refining: After the charge is melted, continue to heat up to 1620℃. After appropriately reducing the power supply, keep the temperature of the molten steel at 1600℃ for 10 minutes to remove the oxide film. During the refining period, always keep the vacuum degree of the melting chamber ≤3Pa.

[0091] (6) Adding alloy: After refining, fill argon gas to 25000Pa, add graphite, ferrosilicon, ferromanganese, ferrophosphorus, ferromolybdenum, ferrotitanium, metallic tin in order, and finally add ferrosulphur. After adding ferrosilium, carry out high-power electromagnetic stirring for 5 minutes. After adding metallic tin, carry out high-power electromagnetic stirring for 5 minutes. After adding ferrosulphur, carry out high-power electromagnetic stirring for 5 minutes, and then let it stand for 3 minutes.

[0092] (7) Casting: The molten steel is cast at a temperature of 1550°C for 2 min into a φ200 mm × 400 mm metal mold. The molten steel solidifies in the furnace and cools to room temperature to obtain a φ200 mm ingot.

[0093] (8) Annealing: Place the ingot in a muffle furnace for annealing at 850°C for 2 h. After the annealing is completed, air cool to room temperature.

[0094] The mass fractions of C and S elements were determined using an ELTRA CS800 infrared carbon-sulfur analyzer, the mass fractions of O, N and H elements were determined using an ONH-2000 oxygen-nitrogen-hydrogen analyzer, and the mass fractions of other elements were measured using an OBLF QSN750 spectrometer. The chemical composition of the sulfur-containing tin-titanium composite free-cutting steel in the embodiment is shown in Table 3.

[0095] Table 3 Composition of sulfur-containing tin-titanium composite free-cutting steel (wt%)

[0096]

[0097] Figure 2 This is an electron microscope morphology of the sulfide of the embodiment of the present invention. It can be seen from the figure that the sulfide uses Ti as the nucleation core and the formed sulfide is approximately circular. This shows that the addition of Ti helps to improve the morphology of the sulfide. Figure 3 is an optical microscope morphology of sulfide in the embodiment, Figure 3 It can be seen that the sulfides are spindle-shaped and elliptical, and the sulfide morphology is very helpful in improving the cutting performance of the material. Figure 4 is the surface scanning energy spectrum of Ti-containing sulfide in the embodiment, Figure 4 It can be seen that the addition of Ti promotes the formation of Ti-containing sulfides. Figure 5 This is the stress-strain curve of the sulfur-containing tin-titanium composite free-cutting steel according to an embodiment of the present invention. It can be seen that there is no obvious yield platform during the stretching process, and continuous yield deformation is presented. Figure 6 This is a scanning electron microscope image of the tensile fracture of the sulfur-containing tin-titanium composite free-cutting steel according to an embodiment of the present invention. Figure 6 It can be seen that the fracture has many uniform and small dimples, which shows that the material has good plastic toughness. Figure 7 The cutting chips of the sulfur-tin-titanium composite free-cutting steel of the embodiment of the present invention (500 rpm, feed rate 0.05 mm) are Figure 7 It can be seen that the chips are evenly distributed and small, and the sulfur-tin-titanium composite free-cutting steel has good cutting performance.

[0098] The sulfides in the examples were analyzed using a Phenom Partical X desktop scanning electron microscope-energy dispersive spectrometer. The area of ​​the sample statistical analysis was 10.123 mm 2 Table 4 shows the statistics of the aspect ratios of the sulfides in the examples. The proportion of sulfides with an aspect ratio of ≤3 in the examples is greater than 95%, and they are mainly spindle-shaped, which is beneficial to improving the cutting performance of steel.

[0099] Table 4 Statistics of aspect ratio of sulfides in sulfur-containing tin-titanium composite free-cutting steel

[0100] Aspect Ratio Proportion % X≤3 96.1 3<X≤5 3.4 5<X≤10 0.3 10<X≤30 0.2 X>30 0

[0101] With reference to the current national standards GB / T228.1-2010 and GB / T19748-2005, a tensile test bar with a diameter of 5 mm and a standard V-notch Charpy impact specimen with a size of 10 mm×10 mm×55 mm were made, and the room temperature tensile and Charpy impact tests were carried out by an MTS Landmark 370 electro-hydraulic servo universal testing machine and an MTS drop hammer impact testing machine to measure the mechanical properties of the embodiments of the present invention. The tensile strength, yield strength, elongation after fracture, section shrinkage and impact toughness of the embodiments are shown in Table 5. As can be seen from Table 5, the tensile strength is ≥700 MPa, the yield strength is ≥600 MPa, the section shrinkage is ≥30%, the elongation after fracture is ≥25%, and the impact toughness is ≥15 J, and the embodiments have good strength and cutting performance.

[0102] Table 5 Mechanical properties of sulfur-containing tin-titanium composite free-cutting steel in Example

[0103]

[0104]

[0105] In summary, the vacuum induction preparation method of the sulfur-containing tin-titanium composite free-cutting steel of the present invention adopts a vacuum induction furnace to smelt and prepare a φ200mm sulfur-containing tin-titanium composite free-cutting steel ingot with a smaller size, which reduces the processing difficulty of the material, shortens the preparation cycle, and improves the material quality; since the sulfur-containing tin-titanium composite free-cutting steel does not contain lead elements, it will not cause pollution to the environment and is in line with the national development strategy of energy conservation and emission reduction; and the method has a simple smelting process, a short process, a wide source of raw materials for steel, and reduces the production cost of free-cutting steel; in addition, the sulfur-containing tin-titanium composite free-cutting steel of the present invention effectively improves the cutting performance of the material by simultaneously adding three free-cutting elements S, Sn and Ti, and its cutting performance is greatly improved compared with free-cutting steel containing only a single cutting element. The sulfide morphology in the sulfur-containing tin-titanium composite free-cutting steel of the present invention is mainly spindle-shaped, and the proportion of sulfides with an aspect ratio of ≤3 is more than 95%. Furthermore, by further annealing the sulfur-containing tin-titanium composite free-cutting steel, it has both good strength and plasticity, and the mechanical properties after annealing reach: tensile strength ≥700MPa, yield strength ≥600MPa, cross-sectional shrinkage ≥30%, elongation after fracture ≥25%, and impact toughness ≥15J. Therefore, the sulfur-containing tin-titanium composite free-cutting steel with high strength, high plasticity and high cutting performance prepared by the present invention can be used to manufacture parts in the automobile, high-speed rail, home appliances, office equipment and other industries to reduce machining costs, improve production efficiency and product competitiveness, and has good application prospects.

[0106] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A vacuum induction preparation method for composite free-cutting steel containing sulfur, tin and titanium, characterized in that: The method comprises: Preheating the alloy raw materials; The alloy raw materials after preheating are vacuum melted in a specific composition ratio; The molten steel after vacuum melting is sequentially mixed with graphite, ferrosilicon, ferromanganese, ferrophosphorus, ferromolybdenum and ferrotitanium under an inert atmosphere, then mixed with metallic tin, and finally mixed with ferrosulphide, and then allowed to stand to obtain a mixed molten steel; wherein, titanium iron, metallic tin and ferrosulfur are added in sequence, stirred and allowed to stand; Casting the mixed molten steel into a mold, and obtaining a steel ingot after cooling to room temperature; Annealing the steel ingot, and air-cooling it to room temperature to obtain a composite free-cutting steel containing sulfur, tin and titanium; The composition ratio of the alloy raw material is: in mass percentage, 0.01% to 0.1% of C, 0.1% to 0.5% of Si, 0.5% to 5% of Mn, 0.1% to 0.5% of Ni, 10.0% to 20.0% of Cr, 0.1% to 1.0% of S, 0.005% to 0.0015% of Mo, 0.01% to 0.015% of O, 0.01% to 0.015% of N, 0.0001% to 0.005% of H, 0.1% to 0.5% of Sn, 0.001% to 0.05% of Ti, P≤0.01%, and the balance is Fe and unavoidable impurities.

2. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 1 is characterized in that: The preheating treatment conditions are: heating the alloy raw material to 150° C. to 250° C. and keeping the temperature for 3 h to 5 h.

3. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 2 is characterized in that: The preheating treatment conditions are: heating the alloy raw material to 250° C. and keeping the temperature for 5 hours.

4. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 1, characterized in that: The alloy raw material comprises: The mass percentage of S is 0.1% to 0.5%; The mass percentage content of Sn is 0.1% to 0.3%; The mass percentage content of Ti is 0.01% to 0.02%.

5. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 1, characterized in that: The vacuum degree during vacuum smelting is controlled to be ≤3Pa; the temperature is gradually increased to a smelting temperature of 1580°C to 1620°C; after smelting is completed, refining is performed at 1580°C to 1600°C and the temperature is kept for 10min to 20min.

6. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 5, characterized in that: The smelting temperature was controlled at 1620°C, and after smelting, it was refined at 1600°C and kept warm for 10 minutes.

7. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 1, characterized in that: The inert atmosphere condition is controlled to be an argon atmosphere of 10000-30000 Pa.

8. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 1, characterized in that: The casting temperature is controlled at 1500°C to 1550°C and the casting time is 1min to 3min.

9. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 1, characterized in that: The annealing temperature is controlled at 800°C to 900°C and the holding time is 1h to 3h.

10. The vacuum induction preparation method of sulfur-tin-titanium composite free-cutting steel according to claim 9, characterized in that: The annealing temperature was controlled at 850°C and the holding time was 2h.

11. A composite free-cutting steel containing sulfur, tin and titanium, characterized in that: The sulfur-tin-titanium composite free-cutting steel is prepared by the preparation method according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Tin-bearing free-machining steel

    US5961747A

  • Composite low-carbon leaded steels and preparation thereof

    CN101280397A

  • Martensitic s free-cutting stainless steel

    CN111989418A

  • High Strength Martensite Type Free Cutting Stainless Steel Making Method Thereof

    KR1020110043192A